Design and Synthesis of Cu@CuS Yolk–Shell Structures with Enhanced Photocatalytic Activity - Li, Qiuyan; Wang, Fan; Sun, Linqiang; Jiang, Zhe; Ye, Tingting; Chen, Meng; Bai, Qiang; Wang, Chao; Han, Xiguang (Nano-Micro Letters, 2017)
Non-spherical Cu@CuS yolk–shell structures are successfully obtained using Cu2O cube templates in a process combining rapid surface sulfidation followed by disproportionation of the Cu2O core upon treatment with a hydrochloric acid solution. By employing the above method, Cu@CuS yolk–shell structures with different morphologies, including octahedral, truncated octahedral, and cuboctahedral shapes, can be synthesized. The void space within the hollow structures provides a unique confined space, where the metallic copper present in the core of a shell can be protected from agglomeration and oxidation. Furthermore, the presence of metal copper in these hollow structures contributes to improvement in the photocatalytic properties of these materials. The application of these Cu@CuS structures indeed shows clearly improved photocatalytic performance. Highlights: 1 Non-spherical Cu@CuS yolk–shell structures with different morphologies, including octahedral, truncated octahedral, and cuboctahedral shapes, are successfully obtained using a strategy combining shell sulfidation and core disproportionation reaction. 2 The as-prepared Cu@CuS structures exhibited clearly remarkable photocatalytic performance.